Isolated metastatic pancreatic adenocarcinoma to the uterine cervix: A case report - Emily M. Hartsough; Britt K. Erickson; Anil Chauhan; Mahmoud A. Khalifa (Gynecologic Oncology Reports, 2019)
The uterine cervix is an uncommon site of metastatic cancer. Specifically, pancreatic adenocarcinoma metastatic to the cervix is an exceptionally rarely reported phenomenon. We encountered a case of recurrent pancreatic adenocarcinoma presenting as a solitary metastasis to the cervix. To our knowledge, this is the only report describing an isolated recurrence of pancreatic adenocarcinoma to the cervix. When diagnosing metastatic disease to the cervix, it is also imperative for the clinician and pathologist to consider histologic mimics, such as the newly described gastric-type mucinous endocervical adenocarcinoma. Metastatic disease to the cervix may benefit from surgical resection. Keywords: Uterus, Cervix, Pancreatic adenocarcinoma, Metastasis, Gastric-type endocervical adenocarcinoma